Gamified Online Radicalization and Counterterrorism Law Reform for Indonesian Adolescents - Ali Masyhar; Feddy Setio Pribadi; Muhammad Azil Maskur; Nadhira Madania Dimarti; Sunusi Dauda (Journal of Law and Legal Reform, 2026)
Indonesia’s Counterterrorism Law (Law No. 5 of 2018) has not regulated one of the rapidly growing radicalization vectors: multiplayer online games, where recruitment is decentralized, extremist narratives are embedded in in-game content, and migration to encrypted platforms operates outside existing regulatory frameworks. This research addresses that normative gap by examining how extremist content is disseminated through online games played by Indonesian teenagers and identifying legal weaknesses that leave this vector unregulated. Using a normative-qualitative approach combining doctrinal analysis, literature review, and exploratory questionnaire data from 46 junior high school students (ages 12–15) in Gunungpati, Semarang, this study analyzes radicalization mechanisms—including narrative infiltration, extremist symbols, and in-game recruitment—through Moghaddam’s Staircase to Terrorism framework and Ware’s Third Generation of Radicalization. The findings indicate significant exposure to ideological recruitment through in-game social features and psychosocial vulnerabilities among respondents, strengthening the doctrinal urgency beyond generalized statistical claims. The doctrinal analysis identified three normative gaps in Law No. 5 of 2018: the absence of due diligence obligations for game operators, the lack of detection and school-based reporting mechanisms, and the failure to recognize children vulnerable to radicalization as subjects of legal protection rather than criminal responsibility. By integrating empirical evidence with doctrinal analysis, this study provides the first legal-empirical account linking online game–based radicalization to Indonesian counterterrorism law and highlights the need to shift from a repressive to a prevention-oriented legal framework through early intervention in digital radicalization.